2015
DOI: 10.1007/978-3-319-11128-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Alzheimer’s Disease EEG Frequency Components with Lempel-Ziv Complexity

Abstract: Abstract-This pilot study applied Lempel-Ziv Complexity (LZC) to 22 resting EEG signals, collected using the 10-20 international system, from 11 patients with Alzheimer's disease (AD) and 11 age-matched controls. This allowed for frequency band analysis as the EEG signals were first prefiltered with a third order Hamming window in the ranges F to F+WHz with both F and W equal to 1-30Hz respectively. Control subjects were found to have a greater signal complexity than AD patients with statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
2
2
0
2
Order By: Relevance
“…The most characteristic feature caused by AD is the reduction in EEG complexity [33-35, 37, 38, 40, 41] compared to normal subjects. This is consistent with other studies [35,38,43,46,56,58,62,64,80,97,98] and shows that EEG complexity measures are potentially a good biomarker for detecting AD. Unlike previous studies, we found that the complexity measures derived from the EEG frequency bands (i.e., delta, theta, alpha, beta, and gamma) provide significantly better performance in detecting AD than the complexity measures derived from whole EEG records.…”
Section: Discussionsupporting
confidence: 93%
“…The most characteristic feature caused by AD is the reduction in EEG complexity [33-35, 37, 38, 40, 41] compared to normal subjects. This is consistent with other studies [35,38,43,46,56,58,62,64,80,97,98] and shows that EEG complexity measures are potentially a good biomarker for detecting AD. Unlike previous studies, we found that the complexity measures derived from the EEG frequency bands (i.e., delta, theta, alpha, beta, and gamma) provide significantly better performance in detecting AD than the complexity measures derived from whole EEG records.…”
Section: Discussionsupporting
confidence: 93%
“…Given the association of EEG activities (e.g., alpha, delta activities) with AD, Al-nuaimi et al [49] they proved that the derivation of EEG complexity based on EEG activities should lead to enhanced performance. This reduction can be measured using different methods e.g., Tsallis entropy (TsEn) [34,59,60], Higuchi Fractal Dimension (HFD) [61], and Lempel Ziv Complexity (LZC) [41,47]. Consequently, EEG complexity can potentially be a good biomarker for AD diagnosis [37] as AD patients exhibit a significant reduction in EEG complexity [37-39, 48, 55, 62, 63].…”
Section: Reduction In Eeg Complexitymentioning
confidence: 99%
“…While biomarkers derived from the EEG complexity analysis are based on non-linear methods (e.g. entropy methods, fractal dimension, and Lempel-Ziv complexity) [44][45][46][47].This chapter describes research into the development of EEG biomarkers that detect AD based on analysis of changes in the EEG. These changes can be quantified as a biomarker of AD.…”
mentioning
confidence: 99%
“…A CLZ é uma medida de complexidade que tem sido usada para analisar os sinais de EEG em pacientes com a Doença de Alzheimer, Transtorno do Déficit de Atenção com Hiperatividade (TDAH), medir o aprofundamento de anestesia, epilepsia dentre outras condições (LEE et al, 2014;SIMONS et al,2015;IBÁÑEZ-MOLINA et al, 2015).…”
Section: Conclusõesunclassified